ENGLISH FOR THE COMMUNITY - PROJECT DESCRIPTION - Nadina Carmen NICOLICI (National Centre for Policy and Evaluation in Education, 2021)
This article is the general presentation of the project "English for the Community" set up by British Council Romania in partnership with the Romanian American Foundation (RAF), and which has as target group about 150 teachers of English as a foreign language in nine counties in Romania, who teach in schools located in villages or small towns. The first stage of the project took place from 2018 to 2020, and a second stage began in March 2021, and it will last until 2023. There are presented details related to the general aim of the project: to provide professional development for the Romanian EFL teachers who teach in lower and upper secondary schools located in areas which have potential to develop ecotourism. The article includes information about the way in which the project has been organized from the beginning up to now, the areas where it takes place, how it has been developing, which steps have been taken, and the impact it has not only on the members of the target group, but on the whole community as well. A special focus is on Teacher Activity Groups (TAGs), an innovative method for Romania, in the benefit of the teachers directly involved in the project. All these are further illustrated by testimonials provided by the members of the target group, the trainers, and the direct and indirect beneficiaries of the program.